Nicaragua : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix examines factors that have determined long-term growth in Nicaragua. Stylized facts suggest that government policies have had a decisive influence on growth. In particular, productivity and capital accumulation suffered during periods of excessive deficit spending and inadequate enforcement of private property rights. A sectoral analysis of growth reveals that liberalization and deregulation in the 1990s led to deep structural changes in the economy. The paper also describes the main characteristics of Nicaragua's tax system, identifying key weaknesses and their economic costs.